2014
DOI: 10.1128/iai.01524-14
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic Clostridium difficile Strains Demonstrate Increased Competitive Fitness Compared to Nonepidemic Isolates

Abstract: Clostridium difficile infection is the most common cause of severe cases of antibiotic-associated diarrhea (AAD) and is a significant health burden. Recent increases in the rate of C. difficile infection have paralleled the emergence of a specific phylogenetic clade of C. difficile strains (ribotype 027; North American pulsed-field electrophoresis 1 [NAP1]; restriction endonuclease analysis [REA] group BI). Initial reports indicated that ribotype 027 strains were associated with increased morbidity and mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 54 publications
(55 reference statements)
4
89
0
2
Order By: Relevance
“…Previous reports [33] suggested that the lack of correspondence between in vitro and in vivo antibiotic activity may be explained by pharmacokinetic properties for MTR -high upper gastrointestinal absorption leading to low concentration in the intestine [35] -or physiological characteristics ensuring survival of the strains. Recent in vivo studies demonstrated the competitive advantage of PR 027 over other ribotypes, the authors suggesting an increased potential of PR 027 strains in using limited environmental resources [36]. Re-colonization of the patient through contact with spore-contaminated surfaces could be another cause of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports [33] suggested that the lack of correspondence between in vitro and in vivo antibiotic activity may be explained by pharmacokinetic properties for MTR -high upper gastrointestinal absorption leading to low concentration in the intestine [35] -or physiological characteristics ensuring survival of the strains. Recent in vivo studies demonstrated the competitive advantage of PR 027 over other ribotypes, the authors suggesting an increased potential of PR 027 strains in using limited environmental resources [36]. Re-colonization of the patient through contact with spore-contaminated surfaces could be another cause of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…10 To investigate potential mechanisms for increased fitness, we examined carbon source utilization in an epidemic RT027 isolate (CD2015) using the Biolog 96-well Phenotype MicroArray carbon source plates (see Methods and Extended Data Table 1). Out of several carbon sources identified that supported CD2015 growth, we found the disaccharide trehalose increased the growth yield of CD2015 by approximately 5-fold compared to a non-RT027 strain.…”
Section: Epidemic Rt027 and Rt078 Strains Can Grow On Low Concentratimentioning
confidence: 99%
“…However, a study conducted by Robinson et al (2014) did not find a difference in the sporulation capacity between hypervirulent and nonhypervirulent strains. The thymidine synthase gene in RT 027 strains could confer a growth advantage for its competitive fitness (Robinson et al, 2014), however, the majority of factors that enhance fitness among epidemic strains of C. difficile are unknown.…”
Section: Difficile In Food Animals and Foodborne CDImentioning
confidence: 83%
“…Although still controversial, some studies have shown that epidemic strains of C. difficile have a higher sporulation capacity than nonepidemic strains and may persist in the environment longer (Merrigan et al, 2010). However, a study conducted by Robinson et al (2014) did not find a difference in the sporulation capacity between hypervirulent and nonhypervirulent strains. The thymidine synthase gene in RT 027 strains could confer a growth advantage for its competitive fitness (Robinson et al, 2014), however, the majority of factors that enhance fitness among epidemic strains of C. difficile are unknown.…”
Section: Difficile In Food Animals and Foodborne CDImentioning
confidence: 99%